Measure 2 : Retention Program : Community Networks and Educational Institutions Components : Prospectus 2014-2018 - Dialogue McGill (2014)
In conformity with the Implementation Framework, this Prospectus addresses Measure 2, the 2014-2018 Retention Program – Community Networks and Educational Institutions Components. McGill University prepared this Prospectus to support the calls for proposals for retention initiatives from the community networks and educational institutions. It presents the structure and content of each of these components of the Program, the objectives, the partners involved, the conditions to be fulfilled, the parameters of the call for proposals and the funding structure. It deals with training and retention incentive initiatives and support measures for students, more specifically promotional projects with health and social services institutions and educational institutions, allocation of bursaries, initiatives to support internship supervisors, professional French language courses for students in the targeted educational institutions, welcoming and community integration measures, language and cultural adaptation activities for professionals from the health and social services network, and outreach activities with extra-regional partners to support the integration and academic success of students studying out of region.

Mesure 2 : Programme de maintien en poste : Volets Réseaux communautaires et Maisons d’enseignement : Prospectus 2014-2018 - Dialogue McGill (2014)
Le Projet de formation et de maintien en poste des professionnels de la santé de l’Université McGill contribue aux initiatives du Québec destinées à assurer aux Québécois d’expression anglaise l’accès dans leur langue à la gamme complète de services de santé et de services sociaux, et ce, au moyen de diverses mesures visant à fournir et à maintenir en poste un complément de main-d’œuvre suffisant, capable d’offrir des services en anglais. Le projet constitue un outil additionnel favorisant l’application et la bonification des programmes régionaux d’accès aux services de santé et aux services sociaux en langue anglaise, conformément à la Loi sur les services de santé et les services sociaux. Ce Projet a pour objectifs précis de susciter des initiatives de formation et de maintien en poste qui fourniront aux professionnels de la santé et des services sociaux l’occasion d’améliorer leur capacité d’offrir des services en anglais, ainsi que l’occasion de travailler là où ils seront en mesure de répondre aux besoins des populations d’expression anglaise du Québec. Le Projet vise également à promouvoir la recherche et le partage de l’information quant aux approches visant à réduire les barrières en matière d’accès aux services de santé et aux services sociaux pour les Québécois d’expression anglaise.

Turn into YES 8 : A Benefit Event and Silent Auction: Sponsorship Opportunity - Youth Employment Services (YES) (2014)

Hughes, Maldoff and Sharp to Receive Goldbloom Awards for Community Contributions - Quebec Community Groups Network (QCGN) (2014)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

Community Learning Centres : Changing Lives and Communities : 2013-2014 Annual Report of CLC Activities : September 2014 - Leading English Education and Resource Network (LEARN) (2014)

Celebrate the English Language Arts Network's 10th Anniversary : ELAN Marks Tenth Year of Creating Stronger Networks for Quebec's English-speaking Artists - English Language Arts Network (ELAN) (2014)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

QCGN is Looking for a Few Good Men and Women - Quebec Community Groups Network (QCGN) (2014)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2014)
Parallel title: 70 Years of Challenge and Change

Community in Movement Forum - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

McGill Community for Lifelong Learning : Operating Rules - McGill Community For Lifelong Learning (MCLL) (2014)

Rapport financier annuel : Année financière terminée le 31 mars 2014 - Jeffery Hale - Saint Brigid's (JHSB) (2014)

Building Communities Together : Laurentians, Outaouais, Quebec Region - Seniors Action Quebec (SAQ) (2014)

Annual Report : 2013-2014 - 4Korners (2014)

Our Story : The New Carlisle Community Learning Centre Developmental Evaluation Report - Chatterton, Tammy; Legault, Emma (Leading English Education and Resource Network (LEARN), 2014)
The New Carlisle Community Learning Centre (NCHS CLC) is one of 37 community schools in Quebec. We are located in a small town on the Gaspesian Peninsula. Many people refer to the location as The Baie Des Chaleur. Our vibrant CLC is located in the town of New Carlisle, within New Carlisle High School. The centre was established to encourage lifelong learning by facilitating access to services and offering support to families, students and community members. The founders believed that a CLC would bridge the noticeable gaps in rural communities like ours, balancing the playing field so that our community would have the same opportunities as more fortunate and larger areas. Therefore, the CLC’s main goal is to link partners together to create a culture of lifelong learning that enhances the capacity of the population to live in healthy vibrant communities.

2013-2014 Annual Report - Cote des Neiges Black Community Association (CDNBCA) (2014)
Striving for excellence since 1972, our organization’s vision and mission is focused on helping Black Canadian families rise above structural inequalities and systemic discrimination. Through our programs and services now more than ever before, we are ready to reaffirm and remember the contribution of Montreal’s Black communities to this society and celebrate our identity and heritage. It is time to allow our unique strengths to become louder than our weaknesses and take strategic steps towards better and sustainable futures. It is time to take care of ourselves, support each other and empower our community to overcome the forces that impede individuals to gain fair access to resources and opportunities. Together we can rewrite our legacy.

Centennial CLC Year 3 Evaluation : Taggin' Our Success! - Elston, Cindy (Leading English Education and Resource Network (LEARN), 2014)
Welcome to Centennial’s Community Learning Centre (CLC) Year 3 evaluation report! In these pages you will find highlights of an evaluation carried out between January-May of 2014. We looked at outcomes of key programs and how they relate to achieving our overall mission and mandate. We designed questions using our Theory of Change (ToC), which has six result areas including the two we focused on this year, Student Success and Community Engagement.

Inclusive Education : Socially Just Perspectives and Practices - Leading English Education and Resource Network (LEARN) (2014)
Number of pages: 318

Annual Activity Report : June 1, 2013 - May 31, 2014 - Literacy Quebec (LQ) (2014)

PACTE Project 2013-2014 : The Power of an Online Presence, a Skill to be Harnessed. - Literacy Quebec (LQ) (2014)
The following project has been completed by Literacy Quebec by a grant from Opération Projets PACTE As a provincial organization, Literacy Quebec’s mandate is to support community-based literacy organizations that provide service to English-speaking adults in Quebec, through training, networking and professional development.

Annual Report : 2013–2014 - NDG Community Council (NDGCC) (2014)

NDG Community Strategic Plan 2013-2016 - NDG Community Council (NDGCC) (2014)

Rapport annuel : 2013–2014 - NDG Community Council (NDGCC) (2014)

Westhaven Sector NDG Montreal - NDG Community Council (NDGCC) (2014)
The Westhaven sector is one of the four identified vulnerable sectors in Notre-Dame de Grace. Saint- Jacques and Sherbrooke Street on the East and West and West Broadway and Connaught on the North and South side bind this neighbourhood. The NDG Community Council approached various stakeholders and key actors within the community including residents, volunteers, employees and private storeowners in order to voice their concerns and visions for Westhaven.

Annual Report / Rapport annuel 2013-2014 - Quebec Community Groups Network (QCGN) (2014)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2014)
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)
Number of pages: 24

Annual Report : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Rapport Annuel : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Annual Report 2013-2014 - Voice of English-speaking Quebec (VEQ) (2014)

Western Quebec Literacy Council: Annual Report: 2013-2014 - Western Quebec Literacy Council (2014)

Winter/Spring 2014 Program Book - Youth Employment Services (YES) (2014)